2015
DOI: 10.1155/2015/578107
|View full text |Cite
|
Sign up to set email alerts
|

Rhein: A Review of Pharmacological Activities

Abstract: Rhein (4, 5-dihydroxyanthraquinone-2-carboxylic acid) is a lipophilic anthraquinone extensively found in medicinal herbs, such as Rheum palmatum L., Cassia tora L., Polygonum multiflorum Thunb., and Aloe barbadensis Miller, which have been used medicinally in China for more than 1,000 years. Its biological activities related to human health are being explored actively. Emerging evidence suggests that rhein has many pharmacological effects, including hepatoprotective, nephroprotective, anti-inflammatory, antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
122
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 58 publications
0
122
0
3
Order By: Relevance
“…As previously reported, DFD contains at least three bioactive compounds, which include rhein, aloe-emodin, and emodin [7]. Previous studies have shown that rhein can attenuate the expression of α -smooth muscle actin ( α -SMA) and the deposition of fibronectin (FN) in rat kidney, which in turn may improve kidney fibrosis [13, 14]. Additionally, emodin was found to be effective in suppressing NF- κ B-mediated TGF- β 1 and FN overexpression, thereby protecting against diabetic nephropathy [15].…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, DFD contains at least three bioactive compounds, which include rhein, aloe-emodin, and emodin [7]. Previous studies have shown that rhein can attenuate the expression of α -smooth muscle actin ( α -SMA) and the deposition of fibronectin (FN) in rat kidney, which in turn may improve kidney fibrosis [13, 14]. Additionally, emodin was found to be effective in suppressing NF- κ B-mediated TGF- β 1 and FN overexpression, thereby protecting against diabetic nephropathy [15].…”
Section: Discussionmentioning
confidence: 99%
“…Rhein is inactive for the inhibition of prolyl-4-hydroxylase in the in vitro screens, indicating that rhein is not a broad spectrum inhibitor of the 2OG-dependent hydroxylases (58). Rhein could moderately inhibit JMJD2A and JMJD2E in vitro, two iron(II) and 2OG-dependent histone demethylases.…”
Section: Panel)mentioning
confidence: 93%
“…Thus, UC imposes a significant socioeconomic burden on society. Pathologically, inflammation, as evidenced by infiltration of neutrophils, macrophages, lymphocytes, and mast cells, occurs in the inner lining of the colon and rectum 16. Intestinal inflammation further disrupts mucosa and submucosa, eventually leading to intestinal ulcers.…”
Section: Introductionmentioning
confidence: 99%